Mobilizing greater crop and land potentials sustainably - Kassam, Amir; Basch, Gottlieb; Friedrich, Theodor; Gonzalez, Emilio; Trivino, Paula; Mkomwa, Saidi (Hungarian Geographical Bulletin, 2017)
The supply side of the food security engine is the way we farm. The current engine of conventional tillage farming is faltering and needs to be replaced. It is faltering because it causes unacceptable level of soil erosion and land degradation, and loss in yield potential, productivity, efficiency, resilience and ecosystem services. ‘Business as usual’ is no longer considered to be a suitable option for the future. This article addresses the supply side issues of agriculture to meet future agricultural demands for food and by industry with the alternate Conservation Agriculture (CA) paradigm (involving no-till seeding and weeding in soils with mulch cover and in diversified cropping) that is able to raise productivity sustainably and efficiently, reduce costly inputs, regenerate degraded land, minimize soil erosion, and harness the flow of ecosystem services. CA is an ecosystems approach to farming capable of enhancing not only the economic and environmental performance of crop production and land management, but also promotes a mindset change for producing ‘more from less’, the key attitude towards sustainable production intensification. CA is spreading globally in all continents at an annual rate of some 10 million hectares of cropland. In 2013–2014, CA covered more than 157 million hectares of rainfed and irrigated cropland and it is likely that its current spread is close to some 200 million hectares. In addition, perennial cropping systems such as orchards and plantations are being transformed into CA systems in all continents. In addition to being a best option for large-scale farmers, CA offers a real pro-poor agricultural development model to support sustainable agricultural intensification for low input smallholder farmers.